TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK HYBRID CONTRACT PADA PEGADAIAN SYARIAH (STUDI KASUS PADA PEGADAIAN SYARIAH TABA CEMEKEH LUBUKLINGGAU) - Ikhsan, Muhammad Miftahul; Zainuddin, Cholidi; Mursid, Fadhilla (Program Studi Muamalah Fakultas Syariah dan Hukum, 2021)
AbstractPegadaian syariah use hybrid contract contain rahn and ijarah. the problem which researcher ask about the Practice Of Hybrid Contracts At Sharia Pegadaian Case Studies On Sharia Pegadaian Taba Cemekeh Lubuklinggau, And Ask About A Review Of Sharia Economic Law On The Practice Of Hybrid Contracts At Sharia Pegadaian Taba Cemekeh Lubuklinggau.Researcher use qualitative research with field approach, use primary data, secondary data and tertiary data. Use data collection techniques through interviews and documentation studies.Based on result researched, the Practice Of Hybrid Contracts At Sharia Pegadaian Case Studies On Sharia Pegadaian Taba Cemekeh Lubuklinggau got five points. The require pawn goods, interest in pawn goods, goods pawn procedure, term used, finance in sharia pegadaian.for require pawn goods and interest in pawn goods accordance with standard operating procedures, but goods pawn procedure, term used, finance in sharia pegadaian didn’t completely appropriate because based on Dewan Syariah Nasional Majelis Ulama Indonesia number 25 of 2002 about pawn with non-transparent contracts, unintelligible term, so hesitate to enter into a contract.Keywords: Hybrid Contract, Mu’nah, Pawn